The economics of a "mixed blessing" effect: A case study of the Black Sea - Duncan Knowler; Edward B. Barbier (Fondazione Eni Enrico Mattei (FEEM), 2002)
Nutrient enrichment of marine ecosystems is regarded as a pressing global environmental problem. For certain marine species it may be a mixed blessing, resulting in damaging ecosystem events, but contributing to primary productivity. Consequently, the impact of enrichment on fishery profits may be positive or negative. This paper develops a method for analyzing such problems, using the example of the Black Sea anchovy fishery. Employing a bioeconomic model that incorporates nutrients directly into fish population dynamics, the problem is formulated in deterministic and stochastic terms. The deterministic model assumes a given ecological state in which nutrients contribute positively to pelagic fish production. The stochastic model recognizes that the planner may take into account the probability of potentially damaging shifts in ecological states due to nutrient enrichment. In this latter model, nutrient abatement has an indeterminate welfare effect, but under certain conditions a marginal change in nutrients generates positive aggregate benefits.
Keywords: Q2; Q20; Q22; 330; Nutrients; Black Sea; Mnemiopsis; anchovy; eutrophication; stochastic; economics; valuation; bioeconomic; Turkey; Gewässerbelastung; Bioökonomik; Fischereiressourcen; Theorie; Schwarzes Meer